The Occurrence and Distribution of Benthic Foraminifera in Tropical Waters Along the Strait of Malacca - Minhat, Fatin Izzati; Ghandhi, Suresh M.; Ahzan, Nurul Syahirah Mohd; Haq, Norizmaira Abdul; Manaf, Omar Abdul Rahman Abdul; Sabohi, Shinazamreena Mhd; Lee, Lee Hin; Akhir, Mohd Fadzil; Abdullah, Maizah Mohd (Frontiers in Marine Science, 2021)
Foraminifera are shelled single-celled protists that are found in all marine environments. Benthic foraminifera either live in sediments or attach to surfaces on the seafloor. Understanding the distribution and ecological response of benthic foraminifera is crucial, as they can indicate past and current ocean conditions. However, the benthic foraminifera distribution along the busy Strait of Malacca, which connects the Indian Ocean (north) to the Java Sea (south), is undersampled. In this study, we collected 24 surface samples from the northern Strait of Malacca to understand the distribution of foraminifera assemblages in shallow tropical waters. A total of 49 species of benthic foraminifera were identified. Calcareous hyaline species dominated the assemblages, with an extremely low occurrence of calcareous porcelaneous species. The common calcareous hyaline taxa were Asterorotalia pulchella, Pseudorotalia schroeteriana, Discorbinella bertheloti, Ammonia tepida, and Heterolepa praecincta. Cluster analysis categorised the foraminiferal assemblages into three major groups. The first cluster (Group A) consisted of a more diverse assemblage of hyaline and agglutinated species that inhabited a mean water depth of 45 m. The second cluster represented a population that inhabited deeper water environments (average water depth of 59 m). Finally, the third cluster (Group C) consisted of a foraminifera assemblage that inhabited shallow coastal environments (average depth of 22 m) with higher organic matter enrichment. The multivariate canonical correspondence analysis (CCA) showed that the foraminiferal assemblages reflected the shallow to deep water transition in the Malacca Strait. Water depth, which defines the depositional environment, had a greater influence on foraminifera distribution here than organic matter and salinity.